Establishment of chicken muscle and adipogenic cell cultures for cultivated meat production - Haach, Vanessa; Silveira, Karine R. D.; Peixoto, Maíra de A.; Sá, Ana Paula Passione e; Gressler, Vanessa; Feddern, Vivian; Ibelli, Adriana M. G.; Silva, Luciano Paulino; Bastos, Ana Paula (Frontiers in Nutrition, 2025)
IntroductionCultured meat seeks to replicate the sensory and nutritional attributes l of conventional meat by developing structured muscle tissue using cell culture. This study focuses on the culture of chicken embryonic and muscle-derived mesenchymal stem cells (MSCs) to derive muscle, and fat, optimizing conditions for differentiation and integration.MethodsWe utilized monolayer and three-dimensional microcarrier-based cultures to produce muscle fibers and adipocytes while maintaining the extracellular matrix (ECM) integrity essential for tissue cohesion. Key pluripotency and myogenic markers (e.g., cOCT4, cMYOD, cMYH1E) were analyzed during differentiation, revealing dynamic gene expression patterns that underscore myogenesis.ResultsMyoblast differentiation into mature myotubes demonstrated decreased cPAX7 (−35%) and increased cMYMK (+67%), confirming lineage commitment and muscle fiber formation. Adipogenesis was induced in embryonic MSCs using food-grade lecithin, which activated PPARγ, C/EBPα, and FABP4,resulting in robust lipid droplet accumulation. To scale production, microcarriers facilitated cell proliferation, while transglutaminase-based stabilization enabled the formation of three-dimensional tissue structures comparable to native meat.ConclusionOur findings highlight advances in culture protocols, genotypic and phenotypic expression analyses of multinucleated chicken muscle and adipocyte cells for cultured meat production.